Nicotine and fluoxetine alter adolescent dopamine-mediated behaviors via 5-HT1A receptor activation - Yuan, Menglu; Leslie, Frances M. (Frontiers in Psychiatry, 2024)
Introduction Abuse or misuse of tobacco, e-cigarettes, or antidepressants may have serious clinical consequences during adolescence, a sensitive period during brain development when the distinct neurobiology of adolescent serotonin (5-HT) and dopamine (DA) systems create unique behavioral vulnerabilities to drugs of abuse. Methods Using a pharmacological approach, we modeled the behavioral and neurochemical effects of subchronic (4-day) nicotine (60µg/kg, i.v.) or fluoxetine (1mg/kg, i.v.) exposure in adolescent and adult male rats. Results Nicotine and fluoxetine significantly enhance quinpirole-induced locomotor activity and initial cocaine self-administration in adolescents, but not adults. These effects were blocked by serotonin 5-HT1A receptor antagonists, WAY-100,635 (100 µg/kg, i.v.) or S-15535 (300 µg/kg, i.v.). Neurochemical and anatomical autoradiographic analysis of 8-OH-DPAT-stimulated [35S]GTPγS reveal that prior exposure to nicotine and fluoxetine results in both overlapping and distinct effects on regional 5-HT1A receptor activity. Both fluoxetine and nicotine enhance adolescent 5-HT1A receptor activity in the primary motor cortex (M1), whereas fluoxetine alone targets prefrontal cortical neurocircuitry and nicotine alone targets the amygdala. Discussion Given their different pharmacological profiles, comparison between WAY-100,635 and S-15535 indicates that postsynaptic 5-HT1A receptors mediate the behavioral effects of prior nicotine and fluoxetine exposure. In addition, within the adolescent M1, maladaptive changes in 5-HT signaling and 5-HT1A activity after nicotine or fluoxetine exposure may potentiate hyper-responsiveness to dopaminergic drugs and prime adolescent vulnerability for future substance abuse.